Neuroeducation and impact on higher education: a systematic review - Huangal-Scheineder, Sebastián; Cieza-Sánchez, Jaime; Diaz-Paredes, Manuel; Arriaga-Delgado, Miguel; Marchena-Tafur, Aurora (International Journal of Evaluation and Research in Education (IJERE), 2024)
The educational system is always seeking to optimize the teaching-learning process through new methodologies. In this sense, there is an effort to improve the student’s academic performance through the acquisition of the desired knowledge that will also last in time. Given this reality, neuroeducation is born as a contribution to the development of the educational system within a scientific basis that understands the way people learn. In this context, the objectives were to determine the impact of neuroeducation in higher education and to describe the current state of strategies based on neuroeducation in the higher educational context. Therefore, a systematic review of the literature was carried out applying the PRISMA method, establishing a periodic range of 5 years (2018-2023). The articles selected in this review were 47 documents. The results showed that this discipline has many benefits for students to learn properly, although teachers have little knowledge about it. Finally, it is concluded that neuroeducation brings with it strategies to improve teaching based on stimuli and motivation, thus achieving a good academic performance by the student.